High-Performance Work Systems on Performance: The Mediating Roles of Engagement and Innovation in Construction Industry - Nuraeni Pou; Ignatius Rinda Laksana; Aditya Winahyo Eka Putra; Rano Kartono Rahim (LP2M IAIN Palopo, 2026)
This study examines the persistent underachievement of project employees’ KPIs at PT XYZ despite increasing organizational profitability by investigating the influence of High-Performance Work Systems (HPWS) on Employee Performance through Employee Engagement and Innovative Work Behavior within a Resource-Based View (RBV) framework. Using a quantitative explanatory and cross-sectional design, data were collected from 208 project-level managerial employees through a five-point Likert-scale questionnaire, exceeding the minimum sample requirement of 163 respondents. Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4 was employed to evaluate both measurement and structural models. The results reveal that HPWS does not directly affect employee performance but significantly enhances employee engagement and innovative work behavior. Both variables act as partial mediators, translating HPWS practices into improved performance outcomes. These findings suggest that HPWS initiatives should emphasize competency development and innovation-enabling mechanisms rather than administrative compliance. Consistent implementation across projects is essential to ensure effective KPI achievement. Future research should adopt longitudinal designs and incorporate contextual variables such as leadership support or psychological safety.